Moral Values Found in Linguistic Politeness Patterns of Bugis Society - Nashruddin Nashruddin; Fiptar Abdi Alam; Abdu Harun (Edumaspul: Jurnal Pendidikan, 2020)
Politeness Strategy is very urgent because it plays an important role in human communication. It is a key point in enhancing the interpersonal relationship and communication. If participants of communication can obey this principle, they can make their expression more tactful; in other hand, if they violate the Politeness Strategy, they may not make the hearers feel good. The objectives of the current research are to: (i) explore the form and the characteristics of linguistic politenessin Bugisethnic people at Pangkep, Barru, and Soppeng with some examples,and (ii) represent the implication of cultural value in Buginese society. The results of this research show the characteristics and the forms of linguistic politeness through some morphemes marked such as prefix ta’, suffix pronouns ta’, ki’, ni, some honorific vocabularies such as idi’, nak, daeng, and some lexemes iye’, tabe’, and strategies of linguistic politeness, namely bald on record strategy, positive, negative, off record strategy. The implication of cultural valueas a basic value such as ethics and language politeness, self-image, courage, solidarity, and cooperation, are also found in this study.